Nutrition et production laitière chez le dromadaire - Narjisse H. (Séminaire sur la digestion, la nutrition et l'alimentation du dromadaire, 1989)
Despite its great importance to increase the value of semidesertic regions, the dromedary is still a neglected species. This animal is particularly adapted to feed to cover much lower nutritional needs than other species thanks to a very efficient microbial digestion, a good water recycling and a quite particular watering rhythm. Milk production is 800 to 4, 000 1 per lactation which lasts from 10 to 12 months. Heat and dehydration do not have marked effects on milk production. Milk composition, comparable to cows, is particularly rich in vitamin C. Only the water content varies according to watering rhythm. Dromedary is a choice animal capable of producing milk in especially hostile environments.
Séminaire sur la Digestion, la Nutrition et l'Alimentation du Dromadaire, 1988/02/27-1988/03/01, Ouargla (Algeria)